Analisis Strategi Pemasaran untuk Meningkatkan Penjualan Menggunakan Metode SWOT dan AHP pada Industri Pembuatan Tahu - Tanisri, Roberta Heni Anggit; Salima, Shelly (JURNAL TEKNIK INDUSTRI, 2022)
UKM Tahu Tambun Selatan is one of the tofu producers located in Bekasi Regency, West Java. UKM Tahu Tambun Selatan produces three types of tofu, namely, cut tofu, jambe tofu, and also fried tofu. During the period from May 2021 to April 2022, it was found that sales of tofu type cut are the least among all other types of tofu. Therefore, UKM Tahu Tambun Selatan wants to change its marketing strategy to increase sales, especially sales of cut tofu type. The process of preparing marketing strategies is carried out using the SWOT method (strength, weakness, oppurtunity, threats) and also the AHP (Analytical Hierarchy Process) method. The results of this study provide five alternative strategies that can be applied by companies, including product marketing carried out using social media, selling even more economical product prices, producing tofu without using chemicals, establishing good cooperation with customer, and create an even more commercial product name to reach a wider market.